2004
DOI: 10.1080/10284150400020482
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hippocampal Plasticity and Cognitive Behavior by Short-term Blueberry Supplementation in Aged Rats

Abstract: During aging, reductions in hippocampal neurogenesis are associated with memory decline indicating a causal relationship. Indeed, insulin-like growth factor-1 (IGF-1), a major activator of the extracellular receptor kinase pathway that is central in learning and memory processes, is also a key modulator of hippocampal neurogenesis. Previously, we showed that age-related declines in spatial memory tasks can be improved by antioxidant-rich diets containing blueberries. In this study, to begin to understand the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(212 citation statements)
references
References 56 publications
8
202
0
2
Order By: Relevance
“…A 2 % (w/w) Montmorency tart cherry dose was chosen based on previous studies in humans (Kelley et al 2006), as well as those conducted in our laboratory demonstrating the beneficial effects of phytochemical-rich berry fruits (i.e., blueberry, strawberry, cranberry, blackberry, black currant, and boysenberry) on cognition, motor function, and suppression of inflammation and oxidative stress in aged animals and accelerated aging models (Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005;Galli et al 2006;Shukitt-Hale et al 2007, 2009aMalin et al 2011). The amount of ground corn was adjusted in the control diet to compensate for the added volume of the freeze-dried cherry powder, in accordance with established methodology (ShukittHale et al 1998;Youdim et al 2000).…”
Section: Dietmentioning
confidence: 99%
“…A 2 % (w/w) Montmorency tart cherry dose was chosen based on previous studies in humans (Kelley et al 2006), as well as those conducted in our laboratory demonstrating the beneficial effects of phytochemical-rich berry fruits (i.e., blueberry, strawberry, cranberry, blackberry, black currant, and boysenberry) on cognition, motor function, and suppression of inflammation and oxidative stress in aged animals and accelerated aging models (Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005;Galli et al 2006;Shukitt-Hale et al 2007, 2009aMalin et al 2011). The amount of ground corn was adjusted in the control diet to compensate for the added volume of the freeze-dried cherry powder, in accordance with established methodology (ShukittHale et al 1998;Youdim et al 2000).…”
Section: Dietmentioning
confidence: 99%
“…Moreover, supplementation with polyphenol-rich blueberries increased IGF-1 expression in hippocampus of aged rats, improving hippocampal plasticity and memory performances (Casadesus et al 2004). In addition, resveratrol supplementation in non-human primates increased working (as did CR) and spatial memory performance (Dal-Pan et al 2011).…”
Section: Calorie Restriction Mimetics: the Case Of Polyphenolsmentioning
confidence: 99%
“…The amount of corn in the control diet was adjusted to compensate for the added volume of the coffee powder or caffeine. The control NIH-31 diet was the same as that used in earlier studies in which other foods were found to be beneficial for mitigating brain aging (Youdim et al 2000;Joseph et al 2003;Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005). The coffee powder, supplied by Kraft Foods Global, Inc. (Northfield, IL, USA), was prepared by lyophilizing brewed coffee.…”
Section: Dietsmentioning
confidence: 99%